DINAMIKA JARINGAN INTELEKTUAL PESANTREN DI SULAWESI SELATAN - Syamsuddin Arief (Faculty of Tarbiyah and Teacher Training Universitas Islam Negeri Alauddin Makassar, 2008)
The dynamic of Muslim scholars' network between South Sulawesi (boarding school) and Haramains is believed to be a factor influencing the discourse of intellectual and Islamic tradition in South Sulawesi in the 20th century. The “traditional Yellow Book” and intensive networking formed a new community consisting of the pilgri-mages, Muslim scholars, boarding school students and the big and growing number of traders. The implication of the networking can be seen from the